2004
DOI: 10.1007/s00380-004-0768-6
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of green tea catechins inhibits neointimal formation in the rat carotid artery injury model

Abstract: It has been shown that green tea catechins (GTC) suppress proliferation of vascular smooth muscle cells (VSMCs) and that epigallocatechin-3-gallate (EGCG), which is a major constituent of GTC, selectively inhibits the platelet-derived growth factor-BB (PDGF-BB)-induced intracellular signaling transduction pathway. Vascular smooth muscle cell proliferation is one of major mechanisms of restenosis following percutaneous coronary intervention. This study tested whether GTC can inhibit VSMC proliferation and preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…For example, EGCG has been shown to bind PDGF receptor and inhibits its signaling in human SMC [11]. Catechins can inhibit the cultured smooth muscle cell invasion through the basement barrier [12] and inhibit neointimal hyperplasia by inducing TIMP-2 overexpression in the rat carotid artery injury model [13]. One of the action mechanisms of EGCG has been described to inhibit the activation of pro-matrix metalloproteinase (MMP)-2 and the activities of membrane type 1-MMP (MT1-MMP) [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, EGCG has been shown to bind PDGF receptor and inhibits its signaling in human SMC [11]. Catechins can inhibit the cultured smooth muscle cell invasion through the basement barrier [12] and inhibit neointimal hyperplasia by inducing TIMP-2 overexpression in the rat carotid artery injury model [13]. One of the action mechanisms of EGCG has been described to inhibit the activation of pro-matrix metalloproteinase (MMP)-2 and the activities of membrane type 1-MMP (MT1-MMP) [14].…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic of TCM and TCM formula is particularly relevant to the inhibition of VSMC proliferation that is often associated with multiple mechanisms. Previous studies indicated that numerous medicinal plants and their components possess inhibitive activity on VSMC proliferation and are effective for attenuation of the restenosis after PTCA by aiming to multiple targets and through multiple mechanisms (Pan et al, 2003;Kim et al, 2004;Wang et al, 2007). But the disadvantages in TCM and TCM formula are also obvious including the crude and inconsistent preparation, unstable quality and the lack of defined mechanism of effects.…”
Section: Discussionmentioning
confidence: 99%
“…TCM formulations have multiple functional components that interact with multiple biological targets, resulting in a holistic effect that can positively influence the development of complex chronic diseases. Many studies (Pan et al, 2003;Kim et al, 2004) showed that a variety of medicinal plants and their ingredients had the ability to inhibit VSMC proliferation and diminish post PCI restenosis. But further studies using standardized TCM extracts are still necessary to investigate pharmacological efficacy and biomechanic pathways.…”
Section: The Effects Of Byhwd and Its Effective Components On Vsmc Prmentioning
confidence: 99%